The Urgency of Education in Economic Development and Human Resources: A Theoretical Perspective - Ninik Sudarwati; Sidrotun Naim (Tadbir : Jurnal Studi Manajemen Pendidikan, 2022)
Problems that hinder economic development and human resources in many cases, one of which is caused by the low quality and level of human education. While there is a doctrine that education does not increase human productivity. Therefore, this study wants to show the urgency of education on economic development and human resources from a theoretical perspective. Education must be seen as a long-term investment and a key prerequisite for growth and development in various sectors, especially the development of the economic and human sectors. A qualitative method with a descriptive approach was used to analyze the data. Research data is obtained from library materials by seriously studying various relevant literature such as books, scientific articles, and other supporting documents, which are considered to be important contributions to the research topic. Research finds that the quality of education affects economic development and human resources. Education has an important contribution to economic growth because of the availability of human resources produced by education itself. In conclusion, education is the key to economic development and human resources. This study suggests that in order to maximize the effect of education on economic development and human resources, it is necessary to consider certain rules that are important to follow, especially education must be directed to be able to answer the challenges of an increasingly complex era and be a solution to the problems faced by humans